FEATURES OF THE COMMUNICATIVE CULTURE OF EDUCATIONAL INSTITUTIONS TEACHERS: THEORETICAL ASPECT (Psychology Travelogs, 2024)
The article carries out a theoretical analysis of the features of the communicative culture of teachers of educational institutions in the scientific psychological literature. Based on the results of the study the essence of concepts is revealed: communication, pedagogical communication, communicative culture, communicative interaction, communicative skills, psychological factors of the communicative culture of teachers, communicative and pedagogical activity. It was determined that communicative culture is a complex, integral and dynamic phenomenon and arises on the basis of accumulated knowledge and skills; is manifested in the ability to communicate effectively and interact successfully. The importance of psychological factors of communication in all aspects of the educational process, in particular, in the socializing and educational sphere, is outlined. The role of communication in professional activity and communicative and professional self-improvement of teachers of educational institutions is considered. Attention is focused on the motivational and value aspect of pedagogical communication, which contributes to the formation of the general social spiritual and value space of educational subjects. Conclusions were made regarding the purposeful psychological preparation of teachers for pedagogical communication, cooperation and effective dialogue with the aim of forming social-communicative competence focused on humanistic principles; the development of psychological features of the communicative culture of teachers is a key element of improving the quality of education.
Keywords: communication; pedagogical communication; communicative culture; communicative interaction; communicative skills; factors of the communicative culture of teachers; communicative and pedagogical activity